Mickey Mouse Muzak: Shaping Experience Musically at Walt Disney World. Issue 1 (16th January 2017) - CAMP, GREGORY
Abstract: The academic assessment of the products of the Walt Disney Company is usually highly negative, drawing out their sexist, racist, and mercenary factors. Although such views are not easily denied, their strong ideology often hides how Disney texts actually operate and how their audiences interact with them. This article explores how recorded music is used in the Disney theme parks to condition audience response, finding a middle ground between an ideological view, exploring the part music plays in social control, and a hermeneutic view, seeing how music functions in articulating and enhancing the experiences in which Disney's guests participate. Disney's Imagineers draw on the language of film music to create a wide variety of narrative musical spaces that give guests the impression that they navigate through these carefully staged narratives as protagonists. Film-musicological models show that guests are encouraged to feel that they control the respective spaces, although filtering the model through critical theory will demonstrate that the spaces can actually be seen as controlling them. While critical theory and structuralist hermeneutics might seem at first like strange bedfellows, analyses of both the narratives themselves and of their social effects can usefully reflect each other, together providing a more nuanced view of Walt Disney World's experiential texts than has been presented either in the academy or by Disney itself.